Warunkowe przedterminowe zwolnienie z odbywania kary pozbawienia wolności w systemie dozoru elektronicznego — przesłanki materialne - Małyniuk, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper includes an analysis of the substantive conditions for the authorization to serve a punishment of deprivation of liberty in the electronic surveillance system. Then those are compared to the conditions for granting of conditional release. As a result of this analysis and comparison conclusions are formulated, concerning the influence of serving the punishment in the electronic surveillance system on the decision about granting of conditional release.
Keywords: warunkowe zwolnienie; dozór elektroniczny